2021
DOI: 10.1088/0256-307x/38/7/077402
|View full text |Cite
|
Sign up to set email alerts
|

S-Wave Superconductivity in Kagome Metal CsV3Sb5 Revealed by 121/123Sb NQR and 51V NMR Measurements

Abstract: We report 121/123Sb nuclear quadrupole resonance (NQR) and 51V nuclear magnetic resonance (NMR) measurements on kagome metal CsV3Sb5 with T c = 2.5 K. Both 51V NMR spectra and 121/123Sb NQR spectra split after a charge density wave (CDW) transition, which demonstrates a commensurate CDW state. The coexistence of the high temperature phase and the CDW phase between 91 K and 94 K manifests that it is a first-order phase transition. At low temperature, electric-field-gradient fluctuations dimini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
74
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(87 citation statements)
references
References 41 publications
12
74
0
1
Order By: Relevance
“…Nonetheless, the CDW appears to couple more strongly to the lattice, such that changes in the phonon parameters become more apparent, suggesting the first-order nature of the phase transition. This is consistent with evidence from nuclear magnetic resonance and nuclear quadrupole resonance measurements in the bulk limit [58][59][60]. These results imply that interlayer interaction tends to smear the CDW lattice distortion.…”
Section: Thickness Dependencesupporting
confidence: 90%
“…Nonetheless, the CDW appears to couple more strongly to the lattice, such that changes in the phonon parameters become more apparent, suggesting the first-order nature of the phase transition. This is consistent with evidence from nuclear magnetic resonance and nuclear quadrupole resonance measurements in the bulk limit [58][59][60]. These results imply that interlayer interaction tends to smear the CDW lattice distortion.…”
Section: Thickness Dependencesupporting
confidence: 90%
“…They undergo a charge density wave (CDW) transition at T CDW = 78 K, 103 K, 94 K and a superconducting transition at T c =0.93 K, 0.92 K, and 2.5 K for A = K, Rb, Cs, respectively. The superconducting state is found to be spin singlet with s-wave pairing symmetry in the bulk state [6][7][8]. STM studies observed possible Majorana modes [9] and pair density wave [10] in the surface state.…”
mentioning
confidence: 93%
“…Single crystals of CsV 3 Sb 5 were synthesized using the self-flux method [6]. Superconductivity with T c = 2.5 K is confirmed by dc magnetization measured using a superconducting quantum interference device (SQUID).…”
mentioning
confidence: 99%
“…Here, the presence of linear bands, Dirac points, and band saddle points (van Hove singularities) in the electronic structure of a nearest-neighbor kagome metal causes multiple electronic instabilities that have been studied theoretically [1][2][3][4] but did not find their way into the lab until the recent discovery of the AV 3 Sb 5 compound family with A = K, Rb, Cs [5]. Both charge-density wave (CDW) order [6][7][8][9][10][11] and superconductivity [12][13][14][15][16][17] observed experimentally in these compounds closely resemble theoretical findings for a simple kagome metal with the Fermi energy lying near the van Hove singularity at the filling level of 5 12 [18,19]. In AV 3 Sb 5 , the corresponding saddle points are clearly visible in the vanadium bands around the M point slightly below the Fermi level (Fig.…”
Section: Introductionmentioning
confidence: 99%